2020
DOI: 10.3390/ma13204568
|View full text |Cite
|
Sign up to set email alerts
|

Response of Palladium and Carbon Nanotube Composite Films to Hydrogen Gas and Behavior of Conductive Carriers

Abstract: To develop a high-performance hydrogen gas sensor, we fabricated a composite film made of carbon nanotubes (CNTs) and palladium nanoparticles. Carbon nanotubes were spin-coated onto a glass substrate, and subsequently, palladium nanoparticles were sputtered onto this film. The response to hydrogen gas was measured during two seasons (summer and winter) using a vacuum chamber by introducing a hydrogen/argon gas mixture. There was a clear difference in the sensor response despite the temperature difference betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Due to the high specific area, CNTs generate sorption sites for gas molecules and exhibit a significant change in resistance due to the charge transfer mechanism at the CNT/metal interface . However, the conventional CNTs have no substantial interactions with hydrogen gas, and research efforts focus either on implementing the composite of metal/CNTs or on using metals as electrodes. , Most of the studies were reported on the combination of CNTs with Pd for hydrogen gas sensors either as electrodes (Schottky-based) or as composites. , …”
Section: Introductionsupporting
confidence: 83%
“…Due to the high specific area, CNTs generate sorption sites for gas molecules and exhibit a significant change in resistance due to the charge transfer mechanism at the CNT/metal interface . However, the conventional CNTs have no substantial interactions with hydrogen gas, and research efforts focus either on implementing the composite of metal/CNTs or on using metals as electrodes. , Most of the studies were reported on the combination of CNTs with Pd for hydrogen gas sensors either as electrodes (Schottky-based) or as composites. , …”
Section: Introductionsupporting
confidence: 83%
“…As shown in Figure 5 , when sensor is exposed to NO gas, gas molecules can be adsorbed on the surface of Au NPs, which can lead to decrease the work function of Au NPs. These lower work function sites can enhance the electron transfer from the Au NPs to SWCNTs network, which in further traps the p-type carriers in the CNT network and resulting in the increase in the resistance of the sensor [ 23 , 62 , 63 ]. However, Material 2 had pH 10 during the functionalization process and that would have deprotonated the -COOH group on the nanotubes and result in the reduced adsorption and hence less interaction with NO gas.…”
Section: Resultsmentioning
confidence: 99%